Strikebreaking & intimidation : mercenaries and masculinity in twentieth-century America - Norwood, Stephen H. (Stephen Harlan), 1951-2023 (Gender & American culture., 2002)
Using a social-historical approach, the author focuses on the mercenaries the corporations enlisted in their anti-union efforts and considers the paramilitary methods unions developed to counter them. The book also traces the economic restructuring which transformed corporate anti-unionism.